The Molecular Determinants of Small-Molecule Ligand Binding at P2X Receptors - Pasqualetto, Gaia; Brancale, Andrea; Young, Mark T. (Frontiers in Pharmacology, 2018)
P2X receptors are trimeric eukaryotic ATP-gated cation channels. Extracellular ATP - their physiological ligand - is released as a neurotransmitter and in conditions of cell damage such as inflammation, and substantial evidence implicates P2X receptors in diseases including neuropathic pain, cancer and arthritis. In 2009, the first P2X crystal structure, Danio rerio P2X4 in the apo- state, was published, and this was followed in 2012 by the ATP-bound structure. These structures transformed our understanding of the conformational changes induced by ATP binding and the mechanism of ligand specificity, and enabled homology modelling of mammalian P2X receptors for ligand docking and rational design of receptor modulators. P2X receptors are attractive drug targets, and a wide array of potent, subtype-selective modulators (mostly antagonists) have been developed. In 2016, crystal structures of human P2X3 in complex with the competitive antagonists TNP-ATP and A-317491, and Ailuropoda melanoleuca P2X7 in complex with a series of allosteric antagonists were published, giving fascinating insights into the mechanism of channel antagonism. In this article we not only summarize current understanding of small-molecule modulator binding at P2X receptors, but also use this information in combination with previously published structure-function data and molecular docking experiments, to hypothesise a role for the dorsal fin loop region in differential ATP potency, and describe novel, testable binding conformations for both the semi-selective synthetic P2X7 agonist 2’-(3’)-O-(4-benzoyl)benzoyl ATP (BzATP), and the P2X4-selective positive allosteric modulator ivermectin. We find that the distal benzoyl group of BzATP lies in close proximity to Lys-127, a residue previously implicated in BzATP binding to P2X7, potentially explaining the increased potency of BzATP at rat P2X7 receptors. Furthermore, to our knowledge, we present the first molecular docking of ivermectin to rat P2X4 receptors, illustrating a plausible binding conformation between the first and second transmembrane domains which not only tallies with previous mutagenesis studies, but would also likely have the effect of stabilizing the open channel structure, consistent with the mode of action of this positive allosteric modulator. From our docking simulations and analysis of sequence homology we propose a series of mutations likely to confer ivermectin sensitivity to human P2X1.